Exploring cardiovascular implications in systemic lupus erythematosus: A holistic analysis of complications, diagnostic criteria, and therapeutic modalities, encompassing pharmacological and adjuvant approaches - Dawi John; Affa Scarlet; Misakyan Yura; Fardeheb Sabrina; Kades Samuel; Kiriaki Anthony; Mohan Aishvaryaa Shree; Norris Brandon; Yoon Sonyeol; Venketaraman Vishwanath (Biomolecular Concepts)
Systemic lupus erythematosus (SLE) poses a diagnostic challenge due to its heterogeneity. This study examines the cardiac complications of SLE comprehensively, covering pericarditis, myocarditis, pleural effusion, valvular disease, atherosclerosis, and cardiac arrhythmias. Nearly one-third of SLE-related deaths are attributed to cardiovascular diseases, necessitating a deeper understanding of cardiac pathophysiology. The impact of SLE on the cardiovascular system manifests in various ways, including recurrent and resistant pericarditis, severe myocarditis, and pleural effusion. Valvular diseases, atherosclerosis, and cardiac arrhythmias are prevalent, with immune complex deposition playing a role in atherosclerosis. Diagnostic criteria involve clinical features, laboratory findings, and autoantibodies, emphasizing the need for early diagnosis and a multidisciplinary diagnostic approach. The review explores pharmacological and non-pharmacological modalities for managing cardiac manifestations in SLE. Recommendations include NSAIDs, colchicine, and proton pump inhibitors for acute pericarditis, while selective immunosuppressive therapy is emerging for myocarditis. Valvular diseases require individualized treatment approaches, and careful corticosteroid management is crucial to avoid increased cardiovascular events. Anti-malarial therapy, particularly hydroxychloroquine, shows promise in mitigating cardiovascular risk factors. Non-pharmacological modifications, such as diet, exercise, and smoke cessation, significantly contribute to cardiovascular health in SLE patients. Adjuvant therapies involving glutathione and glutathione peroxidase focus on redox balance, offering potential interventions. This integrated approach combines diagnostic insights with diverse treatment modalities, providing a holistic strategy for managing cardiac complications in SLE. Ongoing research is essential to refine these strategies and optimize individualized treatment plans for improved patient outcomes.